Ekran i kadr - Hendrykowski, Marek (Wydawnictwo Naukowe UAM, 2002)
Among the contemporary media through which to communicate images, human consciousness is still the most important manner of viewing reality. As it is no technology will replace perception of the world by means of the senses. Consciousness is a peculiar screen, because like any other screens, known for a long time (rock paintings, cinema and TV screens and the like) it always performs the separating function. An important problem is the distinction of a screen from a frame. The screen is the object of perception, and the frame is an imagined object - a conventional framework of a message. The space beyond the frame is an imaginary space which is external to what is perceived by the viewer. In this space a visual plan may be accompanied by an audial plan (e.g. monologue or dialogue "off" the frame). One should always remember (particularly at the time of modern technologies of the media) about the danger of obliterating the border which separates the (audio)visual screen message from reality.
The screen and a frame